Effectiveness–NTU correlation for low temperature PCM encapsulated in spheres - Nasrul Amri, Mohd Amin; Bruno, Frank, Dr.; Belusko, Martin (Elsevier Ltd., 2013)
Link to publisher's homepage at http://www.journals.elsevier.com/